EKSTRAKSI DAN KARAKTERISTIK KIMIA KOLAGEN AKTIF DARI BERBAGAI JENIS KULIT TERNAK - Widya Ramadhini; Husinsyah; Tumrat (Fakultas Pertanian UVAYA Banjarmasin, 2026)
Collagen is a structural protein widely utilized in the food, pharmaceutical, and cosmetic industries. This study aimed to evaluate the chemical characteristics of active collagen extracted from cattle, goat, and broiler chicken skins using bromelain enzyme. The research process included raw material preparation, pretreatment using NaOH and acetic acid, collagen extraction at 40°C, and enzymatic hydrolysis using bromelain. The observed characteristics included yield, moisture content, protein content, ash content, pH value, and degree of hydrolysis. The results showed that cattle skin had the best chemical composition as a raw material, with the highest protein content (35.35%) and the lowest fat content (1.87%). Active collagen produced from cattle skin also exhibited the best characteristics, with a yield of 21.11%, protein content of 70.27%, pH value of 6.06, and degree of hydrolysis of 75.65%. In contrast, active collagen derived from goat and broiler chicken skins showed lower characteristics. Differences in livestock skin types affected the yield, protein content, and degree of hydrolysis of the resulting active collagen. Based on these findings, cattle skin has the greatest potential as a raw material for active collagen production through bromelain-assisted hydrolysis due to its superior chemical characteristics compared to goat and broiler chicken skins.